If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 7 = 2y + 3 Reorder the terms: 7 + 3y = 2y + 3 Reorder the terms: 7 + 3y = 3 + 2y Solving 7 + 3y = 3 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 7 + 3y + -2y = 3 + 2y + -2y Combine like terms: 3y + -2y = 1y 7 + 1y = 3 + 2y + -2y Combine like terms: 2y + -2y = 0 7 + 1y = 3 + 0 7 + 1y = 3 Add '-7' to each side of the equation. 7 + -7 + 1y = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 1y = 3 + -7 1y = 3 + -7 Combine like terms: 3 + -7 = -4 1y = -4 Divide each side by '1'. y = -4 Simplifying y = -4
| 2m(3M)=0 | | 18+7n=-17 | | 3x=-3+30 | | -2(-2x+5)=50+2x | | 2+x-5-2x-7=3x-7 | | (X+4)(3x-12)=0 | | X^2+18=67 | | -i+5+2i+12=12 | | .5d-.2d-17=13 | | 8+(5+2x)=-3 | | 6x-2-3=3x-2 | | X+a=ax+b | | 1/176,1=x/143,9 | | 15+3x=4x-6 | | 44988*93,921=43985*92,781+1003*a | | 2x^2-24=-2x | | y=6x+2-7x^2 | | -2x-3=4x+15 | | 10b^2+43b-9= | | 37-5*6+4= | | x^3+y^3=72 | | cos^2=0.25 | | X+5+10=60 | | 1-(3x-8)=8 | | 6b^2-12b-58=0 | | y=5cos^2x+3 | | z^2+2z-2i+1=0 | | (sinx+1)(cosx-2)=0 | | 3n^2-6n-9=0 | | 0.57=logx | | 3n^2+12n-90=-8 | | k^2-4k-60=0 |